Reaching Out to Mother and Child Through ICDS: Insights from a Field Study in Uttar Pradesh. Issue 2 (August 2017) - Kumar, Nomita P.
Under-nutrition among women and children remains a major development challenge across India. It is recognized that several integrated interventions are necessary to deal with the problem of undernutrition. The Integrated Child Development Services (ICDS) scheme was aimed at improving maternal and child nutrition. A set of broadly agreed nutrition-specific interventions are delivered through network of anganwadi centres (AWCs) along with the continuum of care. Though well-conceived, ICDS has, in practice, given more attention to increasing coverage than to improving the quality of service delivery and to distributing food rather than changing family-based feeding and caring behaviour. This inertia is reflected in poor outcomes in the state of Uttar Pradesh (UP). This article seeks to evaluate the work delivered by ICDS in UP after assessing the allocation and expenditure. This study draws upon the findings of field survey in nine districts of UP conducted by the author recently. Overall, 90 anganwadi centres were covered to find out the kinds of constraints that arise in utilizing funds effectively under this programme. The study also analyses the secondary data to examine the implementation status of ICDS in the state.